GAS BIO DARI HASIL FERMENTASI ECENG GONDOK DUA FASE DAN KAYU LAMTORO SEBAGAI DAHAN BAKAR UNTUK MEMASAK - Tjutju Nurhayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Riogas of 2-phase water hyacinth fermentation and lamtoro wood of 4 years old were used as fuel for cooking by the family. The value of nutrition requirement was 10,353 calories made of rice, meat, fermented soyabean, etc. consumed by 5 persons in the family.The study revealed that bio gas consumptian was 1.281 1. with the caloriffic value of 4,569 Kcal/m3 and methane content of 46.78%. This bio gas energy was 5.85 Mcal for 181 minutes of cooking period. This bio gas consumption can be fulfilled by using 33.14 kg fresh Water hyacinth per day in 300 1 volume reactor and 4.3% dry Water.Lamtoro consumption Was 4, 243 g for 159 minutes of cooking period with the caloriffic vatue of 4,299 Kca/kg and moisture content of 14.50%. This lamtoro enetgy was 18.24 Meal per day per family. The total weight of wood cutting was 164. 80 kg with the moisture content ranged from 44. 74 to 63.33 %. This amount will be enough for cooking for 3 4 days when converted to 14.50 % maisture content.